Evaluation of osimertinib efficacy according to body surface area and body mass index in patients with non‐small cell lung cancer harboring an EGFR mutation: A prospective observational study - Taihei Ono; Satoshi Igawa; Takahiro Ozawa; Masashi Kasajima; Mikiko Ishihara; Yasuhiro Hiyoshi; Seiichiro Kusuhara; Noriko Nishinarita; Tomoya Fukui; Masaru Kubota; Jiichiro Sasaki; Mitsufuji Hisashi; et al. (Thoracic Cancer, 2019)
Background Osimertinib is recommended for non‐small cell lung cancer (NSCLC) patients with EGFR mutation; however, it is unclear whether body size variables affect the efficacy of osimertinib in such patients. This study assessed the potential effect of body surface area (BSA) and body mass index (BMI) on osimertinib chemotherapy in patients with T790M‐positive advanced NSCLC who progress on prior EGFR‐tyrosine kinase inhibitors (TKIs). Methods We conducted a prospective observational cohort study. Median BSA and BMI were used as cut‐off values to evaluate the impact of body size variables on osimertinib chemotherapy. Results The median BSA and BMI of 47 patients were 1.50 m2 and 21.5 kg/m2, respectively. Clinical outcomes did not significantly differ between the high and low BSA groups, with response rates of 59.1% and 56.0% (P = 0.83) and progression‐free survival (PFS) of 7.6 and 9.1 months (P = 0.69), respectively. Similarly, there were no significant differences between the high and low BMI groups relative to response rates, which were 60.8% and 54.1% (P = 0.64), respectively, and PFS, which was 7.6 months in both groups (P = 0.38). No significant differences were observed among toxicity profiles in relation to BSA or BMI. Multivariate analysis identified better performance status, young age, and EGFR exon 19 deletion as independent favorable predictors of PFS. Conclusion The efficacy of osimertinib does not significantly vary relative to body size variables of patients with T790M‐positive NSCLC who progress on prior EGFR‐TKIs.